Atlas of clinical imaging and anatomy of the equine head - Kimberlin, Larry, 1956-; Zur Linden, Alex, 1979-; Ruoff, Lynn, 1951- (Wiley Blackwell, 2017)
Atlas of Clinical Imaging and Anatomy of the Equine Head presents a clear and complete view of the complex anatomy of the equine head using cross-sectional imaging.-Provides a comprehensive comparative atlas to structures of the equine head -Pairs gross anatomy with radiographs, CT, and MRI images -Presents an image-based reference for understanding anatomy and pathology -Covers radiography, computed tomography, and magnetic resonance imaging.